(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Antonin Artaud needs no introduction when it comes to studies of body arts and contemporary art in general. In Artaud – Thought and Body, Kuniichi Uno observes Artaud’s poetics through the lens of the notion of force, which he understands to be present in the artistic processes developed by the poet, screenwriter, and playwright. He explores the variations of this notion in the various registers that make up this work, dividing this set into four phases. The result invites us to rethink, in art education and body arts, the preponderance of the body in its relationship with thought and language.